HUBUNGAN KEPALA DESA DENGAN BADAN PERMUSYAWARATAN DESA DALAM PELAKSANAAN PEMBANGUNAN DI DESA MANLETEN DAN DESA SARABAU KECAMATAN TASIFETO TIMUR KABUPATEN BELU - Nahak, Geraldo Mayella; Tupen, Rafael Rape; Ratu Udju, Hernimus (Petitum Law Journal, 2024)
The village, which is the scope of the organization or is the smallest government structure and is closer to the community, has an important role in carrying out the autonomy mandated by the constitution as a path to a prosperous people. The Village Head has an important role in his position as an arm of the state that is close to the community and as a community leader, while the Village Consultative Body is an institution that carries out government functions. Village governance is a subsystem of the government administration system, so that villages have the authority to regulate and manage the interests of the community. In carrying out a unified government, the relationship pattern between the Village Head and the Village Consultative Body must be balanced and run according to their respective positions, duties and functions, none of which is higher, where both parties have an important role in implementing Village development. This research basically uses juridical-empirical methods. The results of this research show that: (1) The relationship between the village head and the Village Consultative Body is that currently development has not been implemented well from the planning stage to the implementation stage due to poor relations between the Village Head and the Village Consultative Body and (2) Lack of communication channels which can result in miscommunication, misunderstanding and disagreement in development priorities. And the education level of BPD members is also still relatively low.